Intruder in the Dust - Faulkner, William, 1897-1962 (London Vintage, 1996)
Set in the deep south that provided the backdrop for all of Faulkner's finest fiction, Intruder in the Dust is the novel that marks the final phase of its author's outstanding creative period. The chronicle of an elderly black farmer arrested for the murder of a white man and under threat from the lynch mob is a characteristically Faulknerian tale of dark omen, its sole ray of hope the character of the young white boy who repays an old favour by proving the innocence of the man who saved him from drowning in an icy creek.
Keywords: Race relations -- Mississippi -- African Americans--Crimes against